2020
DOI: 10.13106/jafeb.2020.vol7.no12.345
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Responsibility and Job Pursuit Intention of Employees in Vietnam

Abstract: As the Industrial Revolution 4.0 is spreading its wings all over the world and, therefore, also in Vietnam, the logistics industry in Vietnam is facing a severe shortage of human resources in both quantitative and qualitative terms. The role of human resources management (HRM) becomes extremely important. Recruitment is considered the first major function of HRM practices and is the cornerstone of successful in business. In order to improve the recruitment strategy, recruiters need to better understand job pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
(51 reference statements)
1
8
0
Order By: Relevance
“…In addition to this single mediation, CSR could also help GHRM and JPI connect. These findings were consistent with those of Hoang et al (2020), Kumari andSaini (2018), andMoorthy et al (2017). However, the study contradicts the CSR study by Tarigan et al (2021), which showed no connection between environmental CSR and potential employee outcomes.…”
Section: Discussionsupporting
confidence: 84%
“…In addition to this single mediation, CSR could also help GHRM and JPI connect. These findings were consistent with those of Hoang et al (2020), Kumari andSaini (2018), andMoorthy et al (2017). However, the study contradicts the CSR study by Tarigan et al (2021), which showed no connection between environmental CSR and potential employee outcomes.…”
Section: Discussionsupporting
confidence: 84%
“…In this respect, extant research has investigated the relationship between prospective applicants' perceptions about a firm's corporate environmental responsibility (CER) and their intentions to apply for jobs in the firm. However, despite the continuous call for an underlying process via which CER perceptions influence millennials' job-seeking intentions, little research has empirically examined the role of psychological factors in the above relationship [1,2]. Furthermore, while many researchers have focused on the effects of organizational trust on existing employees' performance and commitment (e.g., [3,4]), trust research on job-seeking literature for prospective employees is very limited.…”
Section: Introductionmentioning
confidence: 99%
“…Second, by examining the serial mediating roles of salient psychological factors, this study contributes to the theoretical development of job-seeking literature that until now has not evidently provided clear paths from CER perceptions to job-seeking intentions among millennials in Asian cultures, even far less so in the context of Bangladesh. Third, the present study is expected to expand and integrate two separate streams of previous research on job-seeking literature: (1) research that examined the effects of CER perceptions on job-seeking intentions, but ignored the process through which their effects might occur; and (2) research that investigated how job seekers' perception of organizational trust influenced their intentions to accept a job offered by the company, but overlooked the causal mechanism through which the influence might occur. All in all, this study attempts to extend past research by building a critical bridge between prospective employees' CER perceptions on one side and their job-seeking intentions on the opposite side through exploring the sequential mediating mechanism of organizational trust and job-seeking attitudes in a pre-entry recruitment context.…”
Section: Introductionmentioning
confidence: 99%
“…Abdullah and Abdul Aziz (2013) assert that organizations that consider ethical management practices often believe that a competitive edge can be built through investing in internal stakeholders, particularly employees. Hoang et al (2020) argue that socially accountable and responsible managers focus on strategies that take care of employees. It is argued by Dhanesh (2014) that employees as internal stakeholders often mirror the moral behavior of their managers; therefore, the most responsible and accountable employees are the outcomes of the ethical practices of their managers.…”
Section: Introductionmentioning
confidence: 99%